2005
DOI: 10.1128/jb.187.21.7214-7221.2005
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Conserved S1 and KH Domains in Polynucleotide Phosphorylase

Abstract: We have examined the roles of the conserved S1 and KH RNA binding motifs in the widely dispersed prokaryotic exoribonuclease polynucleotide phosphorylase (PNPase). These domains can be released from the enzyme by mild proteolysis or by truncation of the gene. Using purified recombinant enzymes, we have assessed the effects of specific deletions on RNA binding, on activity against a synthetic substrate under multipleturnover conditions, and on the ability of truncated forms of PNPase to form a minimal RNA degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 32 publications
9
60
0
Order By: Relevance
“…The data suggest that the 25 nt poly(A), too short to bind simultaneously to the central channel of the hexamer and to certain Rrp4 domain(s), is displaced by a next substrate, even if this substrate is shorter. Our observation is in agreement with the two-step model of substrate recognition by E. coli PNPase, and by the proposed key role of its S1 and KH domains for displacement of a stalled substrate and for substrate release [21]. According to this model, a stalled poly(A) degradation product of 25 nt (previously described in Ref.…”
Section: The Rrp4-exosome Strongly Prefers Poly(a)supporting
confidence: 92%
“…The data suggest that the 25 nt poly(A), too short to bind simultaneously to the central channel of the hexamer and to certain Rrp4 domain(s), is displaced by a next substrate, even if this substrate is shorter. Our observation is in agreement with the two-step model of substrate recognition by E. coli PNPase, and by the proposed key role of its S1 and KH domains for displacement of a stalled substrate and for substrate release [21]. According to this model, a stalled poly(A) degradation product of 25 nt (previously described in Ref.…”
Section: The Rrp4-exosome Strongly Prefers Poly(a)supporting
confidence: 92%
“…9). In our model, the 3Ј-end of RNA reaches the catalytic centers through the central channel that can accommodate a single-stranded RNA molecule (10,33). As predicted by the crystal structure of S. solfataricus exosome core (14), the aRrp4 protein may be located at the hydrophobic patches in the opposite side of the ring.…”
Section: Discussionmentioning
confidence: 93%
“…This result is similar to that observed during the preparation of the T (primer-dependent) form of PNPase from the I (primer-independent) form by limited tryptic digestion (36). During the preparation of this manuscript, Stickney et al (33) clearly showed that limited proteolytic digestion removes the RNA binding domains from E. coli PNPase (33), confirming the susceptibility of this region to proteolysis. In that work it is also proposed that the RNA binding domains of PNPase are in an extended conformation (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations